The Role of Networking Capabilities and Spiritual Motivation on School Performance through Dynamic Managerial Capabilities of School Principals (On Integrated Islamic School Network in East Java) - Kholid Kholid; Riesca Anindya Septantina; Lis Indayani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to test and analyse the influence of Networking Capabilities and Spiritual Motivation on School Performance Supported by Dynamic Managerial Capabilities of Principals. This study uses a quantitative approach with respondents in all principals, vice principals and some professional teachers (certified) the object of research was conducted in an integrated Islamic school network in East Java. The results show that there is a greater influence of Networking Capabilities and Spiritual Motivation on School Performance with Dynamic Managerial Capabilities Principal as a mediating variable